Do controle da legalidade às auditorias operacionais: os Tribunais de Contas e o controle financeiro da administração pública brasileira - França, Antonio Marcos Barreto (2012)
The trend of expanding the role of the Courts of Accounts in the national political scene through the mechanisms of control that were assigned to then by the Brazilian Federal Constitution of 1988, before limited to a simple verification of the legality of acts of the public managers, was increased with the mandate to audit the quality of public administration, especially the, efficiency and effectiveness of the policies implemented. In this scenario, the performance audit emerges as an important tool to ensure that these control entities may exercise the task of supervision of the res publica managers in order to ensure that they will always lead the public machine using the most effective public policy to the achievement of positive results for the society. The aim of this study is to verify how the Brazilian Courts of Accounts are dealing with the task of monitoring performance audit issues, answering two basic questions: a) Whether the operational audits carried out by the controlling entities have effectively contributed to the achievement of the public policies’ goals, and; b) If the techniques hitherto used in the performance audits are appropriate for the evaluation of such policies. On the first question, we conclude that the way performance audits have been performed in Brazil, there is a reasonable distance to be travelled before we can answer positively, due to the lack of determination to appoint nominally the responsible for driving the recommendations issued by the Court of Auditors, on the occasion of the publication of the judgment that originates from audit work. On the second question, we believe that the execution of performance audits embraces a large number of factors that goes from the difficulty to obtain policy evaluation indicators that will signalize clearly what goals they tried to reach with such policy, until the needs of the Courts of Accounts to set up specific carriers to do this job.